2021
DOI: 10.1101/2021.08.06.455397
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mitochondrial membrane proteins and VPS35 orchestrate selective removal of mtDNA

Abstract: Integrity of mitochondrial DNA (mtDNA), encoding several subunits of the respiratory chain, is essential to maintain mitochondrial fitness. Mitochondria, as a central hub for metabolism, are affected in a wide variety of human diseases but also during normal ageing, where mtDNA integrity is compromised. Mitochondrial quality control mechanisms work at different levels, and mitophagy and its variants are critical to remove dysfunctional mitochondria together with mtDNA to maintain cellular homeostasis. Understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 78 publications
(103 reference statements)
0
3
0
Order By: Relevance
“…Nonetheless, we propose that the novel mt-HI-NESS fluorescent proteins developed and described here will be valuable tools to study the dynamics of mtDNA nucleoids in live cell imaging experiments. These reporters will allow researchers to address questions about how nucleoids are distributed throughout the mitochondrial network, how mtDNA replication is coordinated with mitochondrial fission and fusion events, and to study release of mtDNA into the cytosol or its endosomal/vesicle-mediated transport to autophagosomes for degradation [56][57][58] .…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, we propose that the novel mt-HI-NESS fluorescent proteins developed and described here will be valuable tools to study the dynamics of mtDNA nucleoids in live cell imaging experiments. These reporters will allow researchers to address questions about how nucleoids are distributed throughout the mitochondrial network, how mtDNA replication is coordinated with mitochondrial fission and fusion events, and to study release of mtDNA into the cytosol or its endosomal/vesicle-mediated transport to autophagosomes for degradation [56][57][58] .…”
Section: Discussionmentioning
confidence: 99%
“…Very recent evidence indicates that the endolysosomal pathway also mediates mitochondrial quality control, either by enhancing mitophagy 34,40 , or by mediating mitochondrial clearance in the absence of autophagy 41 . We demonstrate a role for the endosomal system in the disposal of nucleoids that fail to finish replication and/or segregation, elucidating another pathway of selective disposal of nucleoids, separate from mitophagy 37 . Finally, we propose that endolysosomal extraction of nucleoids represents a third mtDNA release pathway separate from that mediated by BAK/BAX 27,28 or VDAC pores 29 .…”
mentioning
confidence: 87%
“…There is growing evidence for additional pathways beyond mitophagy to maintain mitochondrial quality control, including MDVs 31 as well as piecemeal autophagy of mitochondrial components such as nucleoids 37 and MICOS complexes 38 . Importantly, it was recently demonstrated that mitophagy suppresses mtDNA-driven inflammation 39 .…”
mentioning
confidence: 99%